Supracondylar process of the humerus - A Morphometric Study - Ali Abdul Hameed; Uday Narayan Kudalkar; Nilam Rajesh Madhale (Golestan University Of Medical Sciences, 2024)
Background: The supracondylar process of the humerus, also referred to as the supra-epitrochlear process or supracondylar spur, is a bony protrusion resembling a beak that emerges from the anteromedial surface. It signifies the residual remains of a complete osseous bridge observed in climbing animals. The process is a rare anatomical variation connected inferiorly to the medial epicondyle of the humerus by the ligament of Struthers. Typically presenting unilaterally and located 5-7 cm superior to the medial epicondyle, the supracondylar process holds clinical importance due to its passage it forms with the humerus and the ligament of Struthers. This passage accommodates the median nerve and brachial artery, which may become compressed, leading to neurovascular impingement. The associated symptoms of this compression are exacerbated during hyperextension or pronation of the elbow. Methods: A total of 83 dried humeri were examined at the Department of Anatomy, Goa Medical College, Bambolim, Goa, India. The distal parts of the humeri were assessed for any bony protrusions under daylight conditions. Upon discovery, their dimensions were documented and captured in photographs. Results: Among the 83 dried humeri scrutinized, only one right-sided humerus exhibited an osseous spine on the anteromedial surface. The incidence calculated in this investigation was 1.2%. Conclusion: The supracondylar process has garnered greater attention from anatomists and anthropologists due to its possible implications for the origins and relationships of human races, rather than from clinicians, many of whom are unaware of its infrequent occurrence. The present study, focusing on the Indian population in Goa, reports an incidence of 1.2%, which is relatively high compared to other Indian studies. This data highlights the diversity in the occurrence of the supracondylar process across different ethnic and regional groups, suggesting possible genetic and environmental factors influencing its prevalence.